2022
DOI: 10.3390/biomass2040022
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Apricot Pulp Waste as a Source of Antioxidant Polyphenols and Carotenoid Pigments

Abstract: The interest in extracting bioactive compounds from food processing waste is growing unabated. Apricots are widely consumed worldwide, and many tons of waste are produced annually. Therefore, apricot pulp waste (APW) may serve as a rich source of bioactive compounds. In the present study, we investigated the extraction of antioxidant polyphenols and carotenoid pigments from APW. In both cases, a response surface methodology was employed, so as to optimize the extraction parameters. As regards polyphenols, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, plantderived products are rich in polyphenols, a naturally occurring class of compounds with exceptional antioxidant properties [30]. Polyphenols and their subclass, flavonoids, are present in high amounts in apricots [31]. However, polyphenols are compounds of variable polarity, and as such, their presence in AKO should not be taken for granted.…”
Section: Content Of Polyphenols Flavonoids and Antioxidant Activitymentioning
confidence: 99%
“…However, plantderived products are rich in polyphenols, a naturally occurring class of compounds with exceptional antioxidant properties [30]. Polyphenols and their subclass, flavonoids, are present in high amounts in apricots [31]. However, polyphenols are compounds of variable polarity, and as such, their presence in AKO should not be taken for granted.…”
Section: Content Of Polyphenols Flavonoids and Antioxidant Activitymentioning
confidence: 99%
“…The work presented by Makrygiannis et al [59] focused on the examination of the extraction process for antioxidant polyphenols and carotenoid pigments from discarded apricot pulp. Response surface methodology was utilized in both cases to optimize the extraction parameters.…”
Section: Apricot Kernel Shellmentioning
confidence: 99%
“…Currently, much attention is being paid to the topic of the valorization of fruit byproducts, and their applications in various industries. A recent investigation looked at apricot pulp waste as a source of antioxidant polyphenols and carotenoid pigments and the study concluded that apricot waste can indeed be a rich source of bioactive compounds [112]. Another paper highlighted that plum by-products can be reincorporated into the food supply chain in view of the circular economy due to their antioxidant and antimicrobial activities [113].…”
Section: Applicationsmentioning
confidence: 99%